Do changes in cardiovascular risk factors explain the increasing socioeconomic difference in mortality from ischaemic heart disease in Finland?. Issue 7 (July 1998) - Vartiainen, E; Pekkanen, J; Koskinen, S; Jousilahti, P; Salomaa, V; Puska, P
Abstract : STUDY OBJECTIVE: To estimate the extent to which changes in blood pressure, smoking, and serum cholesterol concentration explain the observed increase in socioeconomic differences in mortality from ischaemic heart disease (IHD) in Finland during the past 20 years. DESIGN: Predicted changes in mortality from IHD were calculated using logistic regression models with the risk factor levels assessed by cross sectional population surveys conducted in 1972, 1977, 1982, and 1987. The subjects included white collar and blue collar workers and farmers. The predicted changes were compared with the observed mortality changes in the same socioeconomic groups in the total population of the same geographical area. SETTING: North Karelia and Kuopio provinces, eastern Finland. PARTICIPANTS: 16, 741 men and 16, 389 women aged 30-59 randomly drawn from the population registers of the study areas. Mortality data were obtained from the total population in the same areas. MAIN RESULTS: In men, the changes in diastolic blood pressure, total serum cholesterol, and smoking predicted a 28% decline in the mortality from IHD among white collar workers, a 30% decline among blue collar workers, and a 33% decline in farmers. Observed declines in the same socioeconomic groups were 61%, 40%, and 37%, respectively. In women, the predicted decline was 41% among white collar workers, 35% among blue collar workers, and 39% among farmers. The respective observed declines were 57%, 43%, and 20%. CONCLUSIONS: Less than half of the decline in IHD mortality among white collar men was explained by the risk factor changes, while they explained 75% of the decline among blue collar men and 89% of the decline among male farmers. Changes in risk factors did not explain the increasing difference in IHD mortality between the socioeconomic groups, especially among men.